Antibacterial and Antioxidant Capacity of Methanol Root Extract of Mangifera Indica - Umaru, Isaac John; Ugbedeojo, Sule John; Tansaba, Akafa Andes; Nanmar, Chakfa; Umaru, Kerenhappuch Isaac; Ugoeze, Egeonu Stephen (African Journal of Biochemistry and Molecular Biology Research, 2024)
Recent years have witnessed enhanced research work reported on plants and plant products. In this regard, plants with traditional therapeutic usage are being screened more efficiently to be considered as a substitution or as a better alternative agent for Human Pathogens. Antioxidant activity, antibacterial, antifungal properties, colour, phytochemical and FT-IR spectral analysis of flowers belonging to Hibiscus moscheutos was determined. Radical scavenging activity of sample extracts were determined based on the percent inhibition of DPPH and ferric reducing antioxidant power (FRAP) assays. Total phenolics were estimated based on the Folin–Ciocalteu method, while, vanillin–HCl and aluminum chloride methods were employed to estimate total tannins and flavonoids in the sample extracts, respectively. To determine total flavonols and anthocyanin contents, spectrophotometric method was employed. For antibacterial activities, modified agar disk diffusion method was adopted. Results: The crude extracts of hexane, dichloromethane, chloroform, ethyl acetate and methanol, extracts with concentration levels at 100, 200, 300 and 400 mg/mL were shown to significantly affect the inhibition of bacterial selected. The presence of phytochemicals compounds possesses the high antibacterial activities of this crude extracts. This study proved that Mangifera Indica crude extracts could be useful for inhibiting the selected pathogens which has an antioxidant potential as well as a natural bacterial agent.